Reduction of CO2 Emissions from Road Transport in Cities Impact of Dynamic Route Guidance System on Greenhouse Gas Emission - Markiewicz, Michal (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2017)
Michal Markiewicz presents the outcomes of his research regarding the influence of dynamic route guidance system on overall emission of carbon dioxide from road transport in rural areas. Sustainable transportation in smart cities is a big challenge of our time, but before electric vehicles replace vehicles that burn fossil fuels we have to think about traffic optimization methods that reduce the amount of greenhouse gas emissions. Contents Comparison of Travel Time Measurements Using Floating Car Data and Intelligent Infrastructure Integration of Cellular Automata Traffic Simulator with CO2 Emission Model Impact of Dynamic Route Guidance System on CO2 Emission Naxos Vehicular Traffic Simulator Target Groups Lecturers and students of computer science, transportation and logistics Traffic engineers The Author Dr. Michal Markiewicz defended his PhD thesis in computer science at the University of Bremen,TZI Technologie-Zentrum Informatik und Informationstechnik, Germany. Currently, he is working on commercialization of his inventions.